Accumulation dynamics of phenolic compounds in the aboveground organs of Euphrasia pectinata Ten., growing in the Central Siberia - V. M. Mirovich (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
A plant of the Euphrasia L. genus is promising to be introduced into medical practice and being used in traditional medicine for eye, gastrointestinal tract, upper respiratory tract disease treatment. Euphrasia pectinata Ten is widespread and growing abundantly in the Central Siberia. Study of the composition and quantitative content of phenolic compounds of Euphrasia pectinata Ten. growing in Irkutsk Region was studied by HpLC method. Organ-specific distribution and dynamics of accumulation depending on the phase of vegetation of 8 compounds (3-O-caffeoylquinic acid(chlorogenicacid), hyperozide, acteoside, cynaroside, diosmetin-7-O-β-D-glucuronide, dihydroquercetin, luteolin, quercetin) were studied. The maximum of flavonoid glycosides is accumulated in flowers and leaves, and the maximum of flavonoid aglycone is accumulated in stems. The maximum quantity of flavonoids in aboveground organs is observed in the flowering period, and maximum of phenylethanoid acteoside is observed in the fruiting period. Thus, as a medicinal plant, the materials can be recommended for harvesting of the aboveground organs E. pectinata during the flowering period.